Peran Biro Organisasi Sekretariat Daerah Provinsi Bali dalam Penguatan Kelembagaan melalui Pengelolaan Fitur Peta Jabatan pada Sistem Informasi Manajemen Kepegawaian (SIMPEG) - Windi Fadhila Cahya Putri; Komang Adi Sastra Wijaya (MASALIQ, 2026)
Institutional restructuring is a strategic instrument for realizing a government organization that is functionally appropriate and right-sized (rightsizing), including in Bali Province, yet its effectiveness is highly dependent on accurate and integrated personnel data management. This study aimed to analyze the role of the Organization Bureau of the Regional Secretariat of Bali Province (Biro Organisasi Sekretariat Daerah Provinsi Bali) in managing the Position Map (Peta Jabatan) within the Sistem Informasi Manajemen Kepegawaian (SIMPEG; Personnel Management Information System) as a support mechanism for institutional restructuring. A descriptive qualitative method was employed, with data collected through in-depth interviews, system observations, and document studies. The findings showed that the Organization Bureau performs multidimensional roles as facilitator, mobilizer, and motivator in ensuring the validity of digitally integrated position data. The Position Map in SIMPEG functions as a single source of truth that enables regional government units to monitor staffing formations and personnel needs in real time. The main constraints include rapid changes in central regulations, disparities in understanding among work units, and technical disruptions to the server. Improvement efforts were undertaken through strengthened cross-sector coordination, regular evaluations, and the implementation of position-formation locking mechanisms to safeguard data integrity. The study concludes that the effectiveness of institutional restructuring is highly contingent upon the synchronization of legal–bureaucratic aspects with the reliability of personnel information systems, making SIMPEG-based Position Map management a critical prerequisite for strengthening the organizational design of regional government units.